In-silico approach of identifying novel therapeutic targets against Yersinia pestis using pan and subtractive genomic analysis. (December 2022) - Islam, Jubairul; Sarkar, Himadree; Hoque, Hammadul; Hasan, Md. Nazmul; Jewel, G.M. Nurnabi Azad
Abstract: The magnitude of human affliction brought about by bacterial infections has been on the rise since the mid-5th century. Yersinia pestis is one such notable, gram-negative bacterium that inflicted havoc around the globe three times throughout different millenniums by causing deadly plagues. Despite the unremitting efforts by scientists, different strains of Yersinia pestis are still affecting the populations in various parts of the world by growing resistant to existing antimicrobial agents owing to their overuse. The current scenario, therefore, calls for new therapeutics to further combat the disease. In this study, 3105 core, 387 pathogen-specific unique, 536 choke-point, 796 virulence factors, and 115 antimicrobial resistant proteins were found using a pan-genomic and subtractive genome analysis of nine Yersinia pestis strains that could be instrumental in the development of drugs against Yersinia pestis . Subsequently, 1461 and 1114 essential proteins were identified as non-homologous to human and gut microflora. 535 and 30 proteins were predicted as cytoplasmic and broad-spectrum targets respectively. Finally, four potential targets were selected for their high connectivity in protein-protein interaction network. These selected target proteins are associated with one of the major lipopolysaccharide biosynthesis pathways. Therefore, dismantling their activity might indicate a probable strategy for developing therapeutics to combat bacterial infection caused by Yersinia pestis . However, further experimental validation in the laboratory is needed to consolidate the research findings. Graphical Abstract: ga1 Highlights: Pan-genomic study of Yersinia pestis reported 3105 druggable core protein targets. Comparative pathway analysis revealed 387 target proteins involved in pathogen-specific pathways. Selection of essential, non-homologous, and cytoplasmic proteins was solely prioritized. Interactome network analysis led to the detection of the top four druggable targets. The findings of this study could be pivotal for antimicrobial drug development against Yersinia pestis causing the classical plague.